Revision of the genus Caracladus with the description of Caracladus zamoniensis spec. nov. (Araneae, Linyphiidae, Erigoninae) - Frick, Holger; Muff, Patrick (Zootaxa, 2009)
The genus Caracladus Simon, 1884 with two Asian and formerly two European species is revised and one new species, Caracladus zamoniensis spec. nov., is described. The new species has been overlooked for over one hundred years. All Caracladus species are diagnosed and described and data on their distribution, habitat and phenology are given. The phylogenetic placement of the genus Caracladus and the relationships between its species are discussed based on 49 morphological characters. Caracladus is deeply nested in the “distal erigonines” with closest relations to Tapinocyba Simon. Detailed illustrations are given for the type species C. avicula (L. Koch, 1869), C. leberti (Roewer, 1942), C. tsurusakii Saito, 1988 and C. zamoniensis spec. nov. Erigone pauperula (Bösenberg & Strand, 1906) nov. comb. (formerly Caracladus pauperulus) is illustrated with some supplementary notes on its description.